Microspectrophotometric DNA analysis in ulcerative colitis with special reference to its application in diagnosis of carcinoma and dysplasia. Issue 11 (November 1990) - Suzuki, K; Muto, T; Masaki, T; Morioka, Y
Abstract : The deoxyribonucleic (DNA) content was measured by microspectrophotometry in 100 specimens from 60 patients with ulcerative colitis, including six patients in whom the colitis was associated with carcinoma. Some 23 of 30 (77%) specimens of dysplastic tissue showed aneuploidy or polyploidy, whereas 50 of 53 (94%) specimens of non-dysplastic tissue showed diploidy. The difference was statistically significant (p less than 0.001). Polyploidy was often observed in non-dysplastic mucosa from patients who had carcinoma or dysplasia. In the non-dysplastic patients all samples of inflamed tissue showed diploidy. Some 10% of samples without inflammation, however, also showed polyploidy. A good correlation was found between the frequency of polyploid cells and the grade of dysplasia. Microspectrophotometric measurement of DNA content proved useful in the assessment and diagnosis of dysplasia in ulcerative colitis and could be considered for screening high risk patients.